Rapid electrochemical synthesis of δ-MnO2 from γ-MnO2 and unleashing its performance as an energy dense electrode. (December 2017) - Yadav, Gautam G.; Wei, Xia; Gallaway, Joshua W.; Chaudhry, Zeeshan; Shin, Amy; Huang, Jinchao; Yakobov, Roman; Nyce, Michael; Vanderklaauw, Nikhil; Banerjee, Sanjoy
Abstract: Birnessite (δ-MnO2 ) is a layered polymorph of manganese dioxide used in a number of applications because of its low cost and non-toxic characteristics. In organic electrolyte battery chemistry's it has been considered as an insertion electrode for lithium, magnesium and other ions. In an alkaline environment, however, it undergoes conversion reactions. It has a high theoretical specific capacity of 617 mAh/g based on two electron reactions making it an energy dense electrode. However, its implementation in practice has been limited due to complicated, time cumbersome synthesis methods, and formation of electrochemical irreversible phases after a few cycles. In this article, we report the rapid synthesis and study of the electrochemical synthesis of δ-MnO2 from cheap and commercially available electrolytic manganese dioxide (EMD, γ-MnO2 ), where we find the formation to proceed from γ-MnO2 to groutite (α-MnOOH) and pyrochroite [Mn(OH)2 ] on the first discharge and follow the reverse transition on the immediate charge to form δ-MnO2 in alkaline electrolyte. The formation process takes only one cycle to completely form δ-MnO2 . The electrochemical reversibility of δ-MnO2 formed through this process is also addressed, where we find that avoiding hydrophobic binders, use of appropriate carbons, addition of certain metallic additives and possibly porosity/pore structure play an important role in unleashing its energy-dense electrochemical performance. Graphical abstract: Highlights: Rapid one step electrochemical synthesis of δ-MnO2 from γ-MnO2 . Uncovering the evolution of δ-MnO2 by XRD, Raman, SEM, EDX, TEM, STEM and real time microscopy. Ensuring maximum reversibility by the use of appropriate binder, carbon and additives. 89–100% retention of 617 mAh/g for over 150 cycles when CNTs, CMC-PVA and bismuth oxide are used with low γ-MnO2 loadings.